The Use of Learning Methods at Talago Biru Indonesian Pencak Silat College Agam Regency Branch - Romi Romi; Jamaris Jamna (Universitas Negeri Padang, 2019)
This research is motivated by the high achievement achieved by the participants of the martial arts training at Talago Biru Indonesian Pencak Silat College Agam Regency Branch in every championship event or festival that he participated in. This can be seen from the achievements of the Pencak silat training participants who competed both at the city, provincial and national levels. Researchers suspect that the cause of the high achievement achieved by the participants of the martial arts training at Talago Biru Indonesian Pencak Silat College Agam Regency Branch was due to the use of effective and efficient learning methods from the trainer. This study aims to describe the process of using instructional methods by trainers in the training activities of Pencak Silat in Talago Biru Indonesian Pencak Silat Education Agam District Branch which is generally seen from several aspects, namely: 1) training objectives, 2) training materials, 3) the ability of trainers and 4) resources and facilities available. The approach used in this study uses quantitative descriptive techniques. The population was 69 people and samples were taken by 52 Pencak silat training participants using a sampling technique that is stratified random sampling. Data collection techniques using a questionnaire distributed to all research samples. The data analysis technique used is the percentage formula. The results of this study indicate that based on aspects in the use of learning methods in martial arts training as a whole looks very good. This is evidenced by the large number of Pencak silat training participants who provide alternative answers and responses